MOUNTAIN SEMERU LAHAR FLOW SIMULATION BASED ON DIGITAL TERRAIN MODEL (DTM) DATA - Hendrawan, Argi
The eruption of Mount Semeru on December 4 2021 caused material and non-material losses. This research aims to simulate lava flows that can be used as a means of minimizing the impact of the disaster. Digital Terrain Model (DTM) data is used to simulate lava flows using the laharz algorithm based on three main processes, namely creating hydrological flows, creating proximal hazard zones and creating distal hazard zones. Simulated lava flows were generated using three flow volume scenarios, namely 5 million m3, 10 million m3, and 20 million m3 which were compared with historical maps of existing lava flow traces and maps of Kawasan Rawan Bencana (KRB) Gunung Semeru. The simulation results show more similarities with the KRB map compared to the historical maps of existing lava flows. Based on the resulting simulation, to maximize mitigation it is recommended to take a safe zone of more than 4 km from the river border.